Data on morphology and biology of the fish rotan Perccottus Glenii Dybowski, 1877 (Perciformes, Eleotrididae) of kuybyshev water reservoir - D. Yu. Semenov (Юг России: экология, развитие)
The article is the first to present information on the ecological peculiarities of habitation for the fish rotan in Kuybyshev water reservoir; its morphometric characteristic, age and sex structure, terms of spawning, prolificacy, feeding, morphological deviations; and also on presence of heavy metals, toxic elements and radioactive nuclides.